Effects of Dental Methacrylates on Oxygen Consumption and Redox Status of Human Pulp Cells. (12th February 2014) - Nocca, Giuseppina; Callà, Cinzia; Martorana, Giuseppe Ettore; Cicillini, Loredana; Rengo, Sandro; Lupi, Alessandro; Cordaro, Massimo; Luisa Gozzo, Maria; Spagnuolo, Gianrico
Abstract : Several studies have already demonstrated that the incomplete polymerization of resin-based dental materials causes the release of monomers which might affect cell metabolism. The aim of this study was to investigate the effects of triethylene glycol dimethacrylate, 1, 4-butanediol dimethacrylate, urethane dimethacrylate, and 2-hydroxyethyl methacrylate on (1) cellular energy metabolism, evaluating oxygen consumption rate, glucose consumption, glucose 6-phosphate dehydrogenase activity, and lactate production, and (2) cellular redox status, through the evaluation of glutathione concentration and of the activities of enzymes regulating glutathione metabolism. Methods . Human pulp cells were used and oxygen consumption was measured by means of a Clark electrode. Moreover, reactive oxygen species production was quantified. Enzymatic activity and glucose and lactate concentrations were determined through a specific kit. Results . Triethylene glycol dimethacrylate, 1, 4-butanediol dimethacrylate, and 2-hydroxyethyl methacrylate induced a decrease in oxygen consumption rate, an enhancement of glucose consumption, and lactate production, whilst glucose 6-phosphate dehydrogenase and glutathione reductase activity were not significantly modified. Moreover, the monomers induced an increase of reactive oxygen species production with a consequent increase of superoxide dismutase and catalase enzymatic activities. A depletion of both reduced and total glutathione was also observed. Conclusion . The obtained results indicate that dental monomers might alter energy metabolism and glutathione redox balance in human pulp cells.